1999
DOI: 10.1099/00207713-49-4-1433
|View full text |Cite
|
Sign up to set email alerts
|

The phylogenetic position of Serratia, Buttiauxella and some other genera of the family Enterobacteriaceae

Abstract: The phylogenetic relationships of the type strains of 38 species from 15 genera of the family Enterobacteriaceae were investigated by comparative 16s rDNA analysis. Several sequences of strains f rom the genera Citrobacter, Erwinia, Pantoea, Proteus, Rahnella and Serratia, analysed in this study, have been analysed previously. However, as the sequences of this study differ slightly from the published ones, they were included in the analysis. Of the 23 enterobacterial genera included in an overview dendrogram o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(83 citation statements)
references
References 15 publications
7
73
0
3
Order By: Relevance
“…Although moderate, these bootstrap values are in the range of those previously reported by 16S rDNA analysis of Enterobacteriaceae (Spro$ er et al, 1999 ;Kwon et al, 1997). Bootstrap values as low as 40 % (Kwon et al, 1997) and 60 % (Spro$ er et al, 1999) have been cited in previous 16S rDNA phylogenetic analyses of Enterobacteriaceae genera.…”
Section: Phylogenetic Relationships Among Klebsiella and Other Enterosupporting
confidence: 62%
See 2 more Smart Citations
“…Although moderate, these bootstrap values are in the range of those previously reported by 16S rDNA analysis of Enterobacteriaceae (Spro$ er et al, 1999 ;Kwon et al, 1997). Bootstrap values as low as 40 % (Kwon et al, 1997) and 60 % (Spro$ er et al, 1999) have been cited in previous 16S rDNA phylogenetic analyses of Enterobacteriaceae genera.…”
Section: Phylogenetic Relationships Among Klebsiella and Other Enterosupporting
confidence: 62%
“…This analysis led us to further study the taxonomic relationships among members of Klebsiella. 16S rDNA sequence comparison has emerged as one of the most powerful tools for investigating bacterial phylogeny (Woese, 1987 ;Weisburg et al, 1991) and its use has resulted in reclassification of bacterial species and genera (Brenner et al, 1993a ;Tamura et al, 1995 ;Rikihisa et al, 1997), including enteric bacteria (Kwon et al, 1997 ;Spro$ er et al, 1999). The level of 16S rDNA sequence similarity has been proposed as a basis for bacterial species definition (Stackebrandt & Goebel, 1994) and the use of polyphasic taxonomy has been advocated to ensure well-balanced determinations of taxonomic relationships (Vandamme et al, 1996).…”
Section: Bergey's Manual Of Systematic Bacteriologymentioning
confidence: 99%
See 1 more Smart Citation
“…As 14 well as other taxon-rich families, members of the Enterobacteriaceae have been subject of extensive analysis of 16S rDNA and taxonomic changes (Spröer et al, 1999;Drancourt et al, 2001). Based on comparative 16S rDNA sequence analysis, it is clear that there is a high degree of relatedness (98% of sequence similarity) between different genera of enterobacteria (Dauga, 2002), and the design of specific probes is very difficult.…”
Section: Discussionmentioning
confidence: 99%
“…revealed similarities of between 99.2 and 99.8% with the different species of the Buttiauxella genus. However, alignment of the sequence obtained in this study for the clinical isolate and the GenBank sequences of B. agrestis, B. gaviniae, and B. noackiae (AJ233400, AJ233403, and AJ233405, respectively [9]) showed that there was sequence polymorphism in our strain in the only region (Escherichia coli position 980 to 1020) where these three species differ according to the GenBank entries. The ambiguities observed contained the bases that, according to published GenBank sequences, differentiate between the three species (Fig.…”
Section: Discussionmentioning
confidence: 99%